Analysis of Organizational Culture and Human Resource Development on Organizational Commitment with Public Motivation as a Mediating Variable at the Medan Sunggal District Office - Rudi Asmara; Erwansyah Erwansyah; Hernawaty Hernawaty (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of organizational culture and human resource development on organizational commitment with Public Service Motivation (PSM) as a mediating variable at the Medan Sunggal Sub-District Office. The study used a quantitative approach with a survey method. The research population consisted of all 90 civil servants at the Medan Sunggal Subdistrict Office, all of whom were included in the sample. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results of the study indicate that organizational culture has a positive and significant effect on organizational commitment, but does not have a significant effect on Public Service Motivation. Human resource development does not have a significant direct effect on organizational commitment, but has a positive and significant effect on Public Service Motivation. Furthermore, Public Service Motivation has a positive and significant effect on organizational commitment. Mediation effect testing shows that Public Service Motivation does not mediate the effect of organizational culture on organizational commitment, but acts as a significant mediating variable in the relationship between human resource development and organizational commitment. These findings indicate that increasing organizational commitment in the Medan Sunggal Subdistrict Office environment is more effectively achieved through direct strengthening of organizational culture and through human resource development that can increase employees' public service motivation. This study provides practical implications for public sector human resource management in designing human resource development policies and strengthening public service values to increase organizational commitment.